ANALISIS PENGARUH INDIKATOR MAKROEKONOMI TERHADAP PENANAMAN MODAL DALAM NEGERI DI INDONESIA PERIODE 2003 - 2012 - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 13 No.2, 2014 JBE UNKLAB, 2014)
This research aimed to explain the effects and causality of interest rates level, exchange rates, inflation, gross domestic product to domestic investment in Indonesia. The time series of this research started from the first quarter of 2003 to the fourth quarter of 2012. Ordinary Least Square (OLS) was used to analyze the data with multiple linear regression approach. The result showed that: (1) interest rates and inflation negatively and significantly impacted domestic investment, (2)  gross domestic product had positive significant impact on domestic investment, (3) exchange rates had a positive insignificant impact on domestic investment, (4)  interest rates level, exchange rates, inflation, and gross domestic product simultaneously had significant impact on domestic investment, (5) gross domestic product had the greatest effect Indonesia’s domestic investment, while  interest rates level, inflation, and exchange rate had lesser effect respectively.